Brown adipose tissue pretending as focal lesion in mesentery of the small intestine – case report and a brief review of literature - Rzucidło, Mateusz; Błotnicki, Michał; Gutkowska, Dorota; Gutkowski, Krzysztof (European Journal of Clinical and Experimental Medicine, 2015)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Brown adipose tissue (BAT) plays a crucial role in a nonshivering thermogenesis process. In the past it was believed that BAT regarded only infants and small children, however, the newest imaging techniques provide sufficient evidence that it also occurs in case of adults. Brown adipose tissue locates mainly in a supraclavicular or a neck region. Much less frequently BAT may be localized around aorta, kidneys and adrenals as well as around greater omentum and colon. Diagnostics of this type of adipose tissue in a body is based primarily on imaging and histopathological examination. In this paper we present a rare case of a 60-year-old patient complying for pain in the abdominal cavity area, who was diagnosed towards proliferative lesion in mesentery of the small intestine, which appeared to be an accumulation of brown adipose tissue. Report has been supplemented by a comprehensive overview of the literature.